Autonomous Vehicles: Moral Dilemmas and Adoption Incentives - Eberhard Feess; Gerd Muehlheusser (Center for Economic Studies and ifo Institute (CESifo), 2022)
In unavoidable traffic accidents, autonomous vehicles (AVs) face the dilemma of protecting either the passenger(s) or third parties. Recent studies show that most people prefer AVs following a utilitarian approach by minimizing total harm. At the same time, however, they would adopt an AV only if it prioritizes the passenger(s), i.e. themselves. As AVs exhibit a lower accident risk in the first place, a regulator therefore faces a trade-off: the harm-minimizing behavior of AVs (ex post efficiency) hampers the willingness to adopt them (ex ante efficiency). Using a game-theoretic model, we analyze how the second-best optimal level of AV passenger protection depends on (i) the AV safety advantage, (ii) the intensity of drivers' social preferences, and (iii) their reluctance to adopt AVs. A higher AV safety advantage may either increase or decrease the second best optimal level of passenger protection.
Keywords: O31; K23; L51; L62; R41; 330; autonomous vehicles; ethical dilemma; trolley problem; adoption of new technologies; game theory